ID: 115. Issue 1 (November 2015) - Lin, Jian-Da; Feng, Ningguo; Sen, Adrish; Balan, Murugabaskar; Tseng, Hsiang-Chi; McElrath, Constance; Durbin, Russell K.; Greenberg, Harry B.; Durbin, Joan E.; Kotenko, Sergei V.
<x xml:space="preserve">Abstract</x> Types I and III IFNs exert common antiviral activities through distinct receptors, and their relative importance for antiviral protection of different organ remains to be fully explored. Mouse strains deficient in type-specific IFN signaling were used to dissect distinct and overlapping contributions of type I and III IFNs to protection against homologous murine (EW-strain) and heterologous simian (RRV-strain) rotavirus infection of the intestine. EW-RV replicated to similar levels in IFN-λR, IFN-αR, IFN-α/λR, IFN-α/γR and STAT1 deficient suckling mice between 2–7 days post-infection (dpi); and only a moderate increase in fecal shedding was observed in IFN-λR and STAT1 knock-out (KO) mice at 8–9 dpi. In contrast, Rag2 KO mice showed chronic viral shedding, demonstrating that the homologous EW-RV efficiently antagonizes murine IFN responses, with viral clearance dependent upon adaptive immune responses. Unlike EW-RV, replication of the heterologous RRV was significantly increased in gastro-intestinal tract of either IFN-λR or IFN-αR deficient mice, and was further enhanced in doubly deficient IFN-α/λR KO animals, demonstrating the sensitivity of RRV to IFN-mediated antiviral protection, and revealing important, and cooperative roles for both type I and type III IFNs in limiting RRV replication. Similarly, both type I and III IFNs helped to limit extra-intestinal RRV spread, whereas type I IFNs were essential for controlling RRV replication in mesenteric lymph nodes. Overall, these results demonstrate a murine host-specific inhibition of IFN's antiviral activity by EW-RV, but cooperative action by type I and type III IFNs in limiting simian RRV growth and spread in mice.